(untitled) (Ameghiniana, 2014)
New dental remains of a chinchillid rodent from Colhuehuapian beds (Lower Miocene) of Chubut province, Argentine, are described. These remains are tentatively referred to Eoviscaccia australis Vucetich, a species only known by two isolated teeth from Deseadan beds. The unworn and little worn cheek teeth show S-shaped occlusal morphology with four crests in the upper and three in the lower teeth, and the enamel is continuous. In little more worn teeth a bilobated configuration is acquired, a thin cement deposit between the laminae appears, and the enamel covering becomes discontinuous. The M3 has a rudimentary third lamina. The first description of the deciduous dentition of a chinchillid is presented herein. These new materials confirm that E. australis is more derived than E. boliviana Vucetich (Deseadan Age, Bolivia) but more primitive than Prolagostomus and Pliolagostomus (Santacrucian and Friasian Ages), due to its degree of hipsodonty, enamel reduction, development of a laminar dental pattern and of the third lamina in the M3.